Modernism in Transition: The Expatriate American Magazine in Europe between the World Wars - Craig Monk (Miscelánea: A Journal of English and American Studies)
The generation of expatriate Americans who spent the period between the world wars in Europe captured the imagination of critics and readers throughout the twentieth century. But while we know their works —and a great deal about their personal excesses— relatively little attention has been paid to the manner in which they facilitated their literary success. For many expatriate Amencan writers, little magazines aided in printing material that commercial publishers would not touch, and the flexibility of these publications allowed the exchange of texts between Europe and the United States. Because modern writers were "self-canonizing", they actually assisted in the "writing" of modernism: we can see many of the threads of the modern canon in these little magazines. But the tension felt by little magazine editors —the tension between an avant-garde impulse to abandon tradition and a more conservative desire to reform art to include their visions— is also inherent in modernism. This essay underlines the importance of the little magazine to modern expatriate American writing, and seeks to further contextulize this writing within modernism itself.